2002
DOI: 10.1021/jf0110248
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Is Required for Poly(phenolic) Domain Formation during Wound-Induced Suberization

Abstract: The requirement for hydrogen peroxide (H(2)O(2)) during suberization was demonstrated in wound-induced potato tubers by monitoring the extent of phenolic polymerization after the inhibition of H(2)O(2) production using diphenyleneiodonium (DPI). In DPI-treated tissues the extent of phenolic polymerization in suberized tissues, measured using DFRC (Derivatization Followed by Reductive Cleavage) and thioglycolic acid analyses, was greatly reduced relative to untreated controls. Concomitantly, a large quantity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 29 publications
(51 reference statements)
2
43
0
Order By: Relevance
“…7). It is well known that H 2 O 2 level could represent a limiting factor in the peroxidase-catalyzed reactions leading to cross-linking of lignin and suberin polyphenolic domain (Razem and Bernards, 2002). Accordingly, G3 treatment decreases the level of polymerized phenols in the wound periderm ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…7). It is well known that H 2 O 2 level could represent a limiting factor in the peroxidase-catalyzed reactions leading to cross-linking of lignin and suberin polyphenolic domain (Razem and Bernards, 2002). Accordingly, G3 treatment decreases the level of polymerized phenols in the wound periderm ( Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Using microsomal fractions from Vicia sativa surface tissues, Kolattukudy and colleagues Kolattukudy, 1977, 1978) demonstrated that cytochrome P450 monooxygenases (P450) are involved in the 蠅-hydroxylation and mid-chain hydroxylation of C16 and C18 fatty acid precursors. Additionally, studies using "wound healing" potato tuber disks as a source of suberizing tissue resulted in the characterization of an NADP-dependent oxidoreductase activity that is required for the formation of diacids from 蠅-hydroxyacids (Agrawal and Kolattukudy, 1978) and provided evidence for the involvement of a H 2 O 2 -dependent peroxidase in the synthesis of aromatic suberin components (Razem and Bernards, 2002;Razem and Bernards, 2003). Finally, the observed properties and fatty acid elongase (FAE) activity in corn root microsomes correlated with the expected qualitative (i.e., chain-length profile) and quantitative requirements for suberin biosynthesis along the root axis (Schreiber et al, 2005a).…”
Section: The Elucidation Of Cutin and Suberin Monomer Biosynthesismentioning
confidence: 99%
“…Peroxidase enzymes, known to catalyse the dehydrogenative polymerization of phenylpropanoids, that can lead to poly(hydroxycinnamates) or lignin, have been found systematically associated with the process of suberization (Borchert 1978;Espelie and Kolattukudy 1985;Razem and Bernards 2002). Anionic peroxidases, isolated from wound-healing potato, catalysed the polymerization of ferulic acid mainly through condensation at the b position (C-8) of the propanoid side chain (Bernards et al 1999).…”
Section: Hydroxycinnamates In Suberin Structurementioning
confidence: 99%